Inhibitor-loaded conducting polymer capsules for active corrosion protection of coating defects. (November 2016) - Pirhady Tavandashti, N.; Ghorbani, M.; Shojaei, A.; Mol, J.M.C.; Terryn, H.; Baert, K.; Gonzalez-Garcia, Y.
Abstract: This work presents the synthesis of nanostructured hollow polyaniline (PANI) capsules and their application for encapsulation of corrosion inhibitor 2-Mercaptobenzothiazole (MBT). The pH-triggered release of MBT from the capsules was evidenced using UV–vis and Surface Enhanced Raman Spectroscopy (SERS). Incorporation of MBT loaded PANI capsules into epoxy ester coating on AA2024-T3 resulted in a protective system with self-healing ability confirmed by Electrochemical Impedance Spectroscopy (EIS) and Scanning Vibrating Electrode Technique (SVET). The results showed that the incorporation of MBT-loaded PANI capsules into the coating has significantly improved its corrosion protection performance due to the interesting smart characteristics of PANI capsules.